Railways and city in territorialization processes in South Africa : from separation to integration - (:unkn) unknown (My University, 2016)
First railway network in Africa, the South African Railways constitute a privileged marker of the territorial mutations that have been shaping this country for decades. The radicalism of political systems shows through the persistency of segregative schemes of which the railways, as part of the planning toolbox, are one of the elements. The inertia of this infrastructure questions its re-appropriation and insertion into the various planning projects over the long term. This thesis approaches the long-term dynamics of 'territorialisation' in South Africa through the prism of railways. This study focuses on the interaction between cities and the railway network, at both the interurban and the intra-urban levels. In order to understand this interaction, cities’ location and railways diffusion patterns are analysed, with a specific emphasis on the shape of the network. Indeed, through their pattern, railways express the intentions of actors in charge of planning at the national level. By the flows it supports and the mobilities it enhances, it gives us information on the socioeconomic requirements of society and the power relations it contains. Thus, this thesis relies on a qualitative and quantitative approach aiming to outline the structuring effects of the railways in South Africa over the long term. Its political use by successive segregationist powers explains partly why nowadays railways keep on marking partition in the post-apartheid urban space and in the practices of city dwellers. However, the recent rail renewal observed in the metropolises, Cape Town in particular, might indicate a possible major inflection in the persistency of inherited dynamics. Indeed, the evolution of the rail offer demonstrates a shift towards a co-construction trend between South African society and urban planning unheard of until now.
Keywords: African Research